A systematic review of emerging trends in crop cultivation using soilless techniques for sustainable agriculture and food security in post-pandemic - Salisu, Monsuru Adekunle; Oyebamiji, Yusuf Opeyemi; Ahmed, Omowunmi Kayode; Shamsudin, Noraziyah A; Fairuz, Yusoff Siti; Yusuff, Oladosu; Yusop, Mohd Rafii; Sulaiman, Zulkefly; Arolu, Fatai (AIMS Press, 2024)
By 2050, the global population is anticipated to reach 10 billion, marking a significant 34% increase and raising concerns regarding food availability. Challenges such as the recent pandemic, which led to workforce and input shortages in agriculture, have made it difficult for many countries to maintain adequate food self-sufficiency (SSL). It is crucial to explore various farming methods to ensure that food remains available and affordable, especially in urban areas where over 55% of the population resides. Traditional agriculture faces issues like poor soil and excessive fertilizer use, which harm the environment. These factors threaten sustainable agriculture and food security, particularly in urban environments. Adopting sustainable soilless technology can enhance urban agriculture by providing a controlled environment for producing healthy food and addressing these challenges post-pandemic. This review, utilizing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework, a widely recognized and rigorous method for conducting systematic reviews, focused on urban agriculture, specifically soilless technologies, as emerging trends in crop cultivation. It examined conventional and cutting-edge urban production systems aimed at promoting sustainable agriculture and food security. The review examined soilless farming techniques such as aeroponics, hydroponics, and aquaponics, highlighting their environmental impact, resource efficiency, and water usage. It carefully considered the advantages and disadvantages of these technologies compared to conventional soil-based farming. Furthermore, the review showcased the successful cultivation of various fresh vegetables and fruits using soilless technologies, each with advantages supporting urban agriculture and overall food security. The findings suggest that these innovative strategies hold promise in fostering sustainable urban agriculture and ensuring food security during a pandemic. These results lay the groundwork for establishing a framework to assess the sustainability of urban agricultural strategies and their practical application in real-world scenarios.